Rhabdomyolysis and Resultant Acute Renal Failure due to Legionella Pneumonia in a Patient with Human Immunodeficiency Virus - Margaret Kypreos; Roma Mehta (Case Reports in Nephrology)
Legionnaires’ disease is a severe pneumonia caused by Legionella that results in laboratory abnormalities including hyponatremia and elevated liver enzymes. Rarely skeletal muscle and renal abnormalities occur. This case report describes a case of Legionella pneumonia complicated by rhabdomyolysis and acute renal failure in a patient with the human immunodeficiency virus.